O efeito do laser de baixa intensidade na parestesia associada à cirurgia ortognática: um ensaio clínico randomizado, duplo cego - Lima, Barbara Betty de (2023)
Dentalfacial deformities result from deficiencies in the growth and development of the maxillomandibular complex and presents orthosurgical treatment as na alternative for its correction. The incidence of alterations in sensitivity resulting from injuries to sensitive nerves by dental procedures represents 64,4%, and orthognathic surgery represents 12,3% of these alterations. Bilateral mandibular ramus sagittal osteotomy is related to the incidence of sensory disturbances of the inferior alveolar nerve (IAN) showing great variations. Complete loss of sensation can result from a subtle change in tactile sensitivity, which can be temporary or permanente. The objective of this study was to investigate the application of low-intensity laser in the treatment of sensory alterations associated with IAN after orthognathic surgery. The sample consisted of 10 patients, with no significant difference between age groups (p=0.454). They were randomly distributed into two groups, where the experimental group (A) received laser treatment in the regions innervated by the intra-oral and extral-oral IAN at different study times, and group B did not receive laser therapy. All patients were evaluated preoperatively and postoperatively (7, 30, 90 and 180 days) using subjective and objective tests. The objective tests were carried out with the aid of monofilament brushes (Semmes-Weinntein), and the subjective evaluation through the use of a questionnaire. The response to the application stimulus with the use of monofilaments did not demonstrate significant variations between groups A and B. However, there was a significant increase in responses to the tactile stimulus from T1 to T3 and T4. Regarding the subjective analysis, there were no statistical differences between groups Aand B in the preoperative evaluation (T0). In the assessment on the 7th postoperative day (T1), there was a statistically significant difference between groups A and B in relation to the sensory alteration itching with p=0.02. Subjective responses related to the value of changes and sensory abnormalities using the visual analogue scale (VAS) did not demonstrate statistical defference between groups A and B at the times evaluated. The neural tissue response to low-intensity laser is evident, but these results may vary in terms of wavelength, irradiation parameters, and dosimetry used. This highlights the need for further clinical studies to develop safe and effective protocols.